Metapoesia: para uma poética da poesia - terceira parte: o poeta - Lima, Enoque Balbino (Semina: Ciências Agrárias, 1982)
The Poem - Third and last part of a Thesis - METAPOESIA - presented no Pontifícia Universidade Católica de Porto Alegre as part of the requirements in order to obtain the degree of full-professorship. In the present study, founded on field-work" and on the metalanguage of the modern poetry, are discussed the concept, nature and species of poems. Poem, in this research, is understood not only the conventional poem but all poetic expression (mythic) of the life and the nature. In this article is discussed particulary the poem. The written poem, verbal discourse ("the poem which Poet wrote"); the poem of the life ("The poem which Somebody wrote"), and of the nature ("the poem which Nobody wrote").